MANAJEMEN PESERTA DIDIK Perencanaan dan Pengorganisasian - Yusuf, Juhaeti (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2019)
Achieving educational goals in schools is strongly influenced by the factors of students. All activities in the school lead to learners and the existence of student acts as subjects as well as objects in the education process at school. In this connection the management of students needs to get serious attention from managerial holders at school. This study focused on the management of students in integrated Islamic junior high school Islamic Boarding School with its sub-focus: (1) new student admissions consisting of registration systems, selection systems and graduation determination systems, (2) fostering students consisting of coaching discipline, fostering academic and non-academic activities, and (3) graduation and alumni searches consisting of graduation and alumni search results. The approach used is a qualitative approach with a multi-case study design. Data collection techniques are carried out through: observation, documentation and in-depth interviews. After checking the validity, the data is analyzed by (1) data reduction, (2) data presentation and (3) drawing conclusions. The results of the study showed that students' planning must be prepared as early as possible at the beginning of each school year. Organizing students starts from grouping classes based on test results so that the formation of superior classes and fostered classes is formed. Then the principal gives responsibility and authority to the homeroom teacher to foster and direct the students.